Capacity of antiretroviral therapy sites for managing NCDs in people living with HIV in Zimbabwe - Laston Gonah; Indres Moodley; Khumbulani Hlongwana (AOSIS, 2020)
Background: There are marked inconsistencies in prevalence data for human immunodeficiency virus and non-communicable disease (HIV-NCD) comorbidity in Zimbabwe. Objectives: To explain these discrepancies, we investigated the capacity of antiretroviral therapy (ART) sites in managing hypertension (HTN) and diabetes mellitus (DM) in people living with HIV (PLWH) in Gweru district, Zimbabwe. Method: This was a qualitative research design in which key informant interviews were conducted with eight health managers, and 12 focus group discussions (FGDs) were conducted with 72 PLWH concurrently diagnosed with HTN and/or DM. Thematic data analysis was performed in NVivo version 12®. Results: Routine screening for HTN and targeted screening for DM were often interrupted by dysfunctional machines and intermittent supply of necessary consumables, impacting negatively on the capacity of the sites to monitor and screen for the NCDs. Erratic hypertensive and diabetic medication availability at study sites were also reported, forcing patients to turn to other treatment options (medication rationing or overdose or sharing, use of home remedies and traditional medicines, and reliance on faith and traditional healers). Conclusion: Findings demonstrate that the quality of observed incidence and prevalence data for HTN and DM in LMICs is a function of the capacity of health centres to screen for NCDs. Given the ageing population of PLWH in sub-Saharan Africa, coupled with increasing trends in the prevalence of NCDs in HIV-infected people, HIV programmes have not evolved with the changing needs of PLWH. Attention to the holistic management of PLWH is long overdue.